1993
DOI: 10.1177/019262339302100404
|View full text |Cite
|
Sign up to set email alerts
|

Multinucleated Hepatocytes Induced by Rifabutin in Rats

Abstract: AESTRAC~Rifabutin is an antibiotic of the rifamycin class, which is particularly active against mycobacteria, including those that occur in AIDS patients. Because clinical use will include long-term therapy, an extensive battery of long-term toxicity studies was carried out by the oral route, including carcinogenicity studies. An interesting feature was the occurrence of multinucleated hepatocytes (MNHs) in the rat. In some instances, as many as 25 nuclei occurred in a single cell. Light microscopy revealed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…These abnormal cells may be found in aged mice, but they have been reported at younger ages in xenoestrogen-exposed rats and may be associated with increased hepatocyte proliferation (Hayashi et al 2008; Scampini et al 1993). Our data on increased multinucleated hepatocytes represent increased ploidy in mice without visible liver masses.…”
Section: Discussionmentioning
confidence: 95%
“…These abnormal cells may be found in aged mice, but they have been reported at younger ages in xenoestrogen-exposed rats and may be associated with increased hepatocyte proliferation (Hayashi et al 2008; Scampini et al 1993). Our data on increased multinucleated hepatocytes represent increased ploidy in mice without visible liver masses.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the detachment of RCs from the remaining fiber and the fusion of tumor cells resulting in MNCs were found. Given that ECMs have been reported to play a role in sustaining tumor tissue structure, cell adhesion and proliferation in HCC 21 and that multinucleated hepatocytes are known to occur along with the deterioration of the environment surrounding hepatocytes, 22 RCs and MNCs might possibly result from changes in the ECMs. Kwack et al have reported that the adhesion of HCC cells to collagen type I and fibronectin was decreased by GPC3 expression, leading to the stimulation of cellular migration and invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…These multinucleated cells are not associated with proliferative changes, but are accompanied by centrilobular hepatocellular hypertrophy, increase in transaminases, bilirubin, and cholesterol. In rats, males have displayed greater sensitivity than females to multinucleation produced by rifabutin, colchicine, thiourea, and methotrexate (109). Adaptive effects lead to hyperplasia of organelles, mainly endoplasmic reticulum and peroxisomes, which leads to compensatory hepatocellular hypertrophy as increase in functional demand leads to organelle expansion (Figure 2).…”
Section: Hepatic Adaptive and Adverse Effects Adaptationmentioning
confidence: 99%